Insidious incrementalism: The silent failure of the microcirculation with increasing peripheral vascular disease risk. (February 2017) - Lemaster, Kent; Jackson, Dwayne; Goldman, Daniel; Frisbee, Jefferson C.
Abstract: This review summarizes material presented in "Adaptive Outcomes of Microvascular Networks to Obesity and Type II Diabetes/Insulin Resistance" on July 30, 2016, at the Joint Meeting of the American Physiological Society and the Physiological Society, in Dublin, Ireland. We discuss the poor predictive power of traditional markers of vascular dysfunction for functional outcomes of muscle fatigue‐resistance and active hyperemia within the setting of elevated peripheral vascular disease risk. Using the obese Zucker rat model of the metabolic syndrome, we describe how blood flow distribution at arteriolar bifurcations (γ) is altered with PVD risk reflecting increased spatial heterogeneity of distribution within networks. The ability of the microvasculature to compensate for increased heterogeneity is attenuated in OZR, creating a condition wherein the inability to match perfusion to local demand is entrenched and made more difficult to overcome. This appears to be an incremental process, as multiple models of increased PVD risk manifest incremental shifts to the spatial and temporal behavior of γ. These data suggest that γ, a superior predictor of functional outcomes for skeletal muscle, may represent a broadly applicable concept that can inform us about system behavior, with health and increased disease/disease risk, and with imposition of therapeutic regimens.